THE INFLUENCE OF FINANCIAL INCLUSION, ACCESS TO FINANCING, AND TECHNOLOGICAL INNOVATION ON MICRO, SMALL, AND MEDIUM ENTERPRISES GROWTH IN KUPANG CITY - Zainuddin Adang Djaha; Selfesina Samadara; Jennie Sarlota Sir; Herni Sunarya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This research examines the influence of financial inclusion, access to financing, and technological innovation on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Kupang City. Methods: The population in this study was MSME entrepreneurs, especially ikat weavers, totaling 357 business units. The number of samples used in this study was 189 respondents. The sampling technique was the Slovin method. Data Analysis Techniques used included instrument validity and reliability tests, partial influence tests (t-tests), and simultaneous influence tests (F-tests). Results: The results indicate that financial inclusion and access to financing have a positive and significant influence on MSME growth, with significance values of 0.014 and 0.001, respectively. Meanwhile, the effect of technological innovation on MSME growth is insignificant, with a significance value of 0.286. Simultaneous analysis also shows that these three factors together have a positive and significant influence on MSME growth, with an F-value of 2.984, which is greater than the F-table of 2.650Conclusion and suggestion: Based on these results, recommendations include improving financial literacy, expanding access to financing through more accessible financing products, and encouraging the adoption of digital technology by MSMEs. Furthermore, the importance of policies that support MSMEs and strengthening collaboration between the government, financial institutions, and MSME players are also key to creating an ecosystem that supports MSME growth in Kupang City. By implementing these recommendations, it is hoped that MSMEs can grow more rapidly, increase their competitiveness, and contribute more to the local economy. Keywords: Access to Financing, Economic Growth, Financial Inclusion, Technological Innovation